Pitting Corrosion of Ni3(Si,Ti) Intermetallic Compound at Various Chloride Concentrations - Gadang Priyotomo (International Journal of Science and Engineering, 2013)
The pitting corrosion of Ni3(Si,Ti) intermetallic compound was investigated as function of chloride concentration by using electrochemical method and scanning electron microscope in sodium chloride solutions at 293 K.  In addition, the pitting corrosion of type C276 alloy was also studied under the same experimental condition for comparison.  The pitting potential obtained for the intermetallic compound decreased with increasing chloride concentration.  The specific pitting potential and pitting potential of Ni3(Si,Ti) were lower than those of C276 alloy, which means that the pitting corrosion resistance of C276 alloy was higher than that of Ni3(Si,Ti).